2014
DOI: 10.1039/c3nr03811d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nanocrystal response and high temperature growth of carbon nanotube–ferroelectric hybrid nanostructure

Abstract: A long standing problem related to the capping of carbon nanotubes (CNT) by inorganic materials at high temperature has been solved. In situ dynamic response of Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) nanocrystals attached to the wings of the outer surface of PZT/CNT hybrid-nanostructure has been demonstrated under a constantenergy high-resolution transmission electron microscopy (HRTEM) e-beam. PZT nanocrystals revealed that the crystal orientations, positions, faces, and hopping states change with time. HRTEM study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The shift in Raman peaks gives the information of the stress level of the MWCNTs [32]. In our case, because the observed shift there is quite small stresses developed at the interface are not so strong, as observed for example for MWCNTs covered with PZT by pulse laser deposition [10,11]. The change in the intensity ratio of D and G bands (I d /I g ) is 1.0 and 1.2 for the MWCNTs and BFO coated VA-MWCNTs of this study, respectively.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The shift in Raman peaks gives the information of the stress level of the MWCNTs [32]. In our case, because the observed shift there is quite small stresses developed at the interface are not so strong, as observed for example for MWCNTs covered with PZT by pulse laser deposition [10,11]. The change in the intensity ratio of D and G bands (I d /I g ) is 1.0 and 1.2 for the MWCNTs and BFO coated VA-MWCNTs of this study, respectively.…”
Section: Resultsmentioning
confidence: 76%
“…VA-MWCNTs used in this work depict two characteristic peaks at 1336 and 1575 cm -1 corresponding to D and G band respectively, where the D band is attributed to the breathing vibration of aromatic rings of carbon in the lattice, indicating the defect level of CNTs and G band corresponds to E2g mode where atoms of the carbon unit cell vibrate tangentially to each other [34]. After the BFO deposition the D and G band of MWCNTs shift to high frequency by ~2 cm -1 and the full width half maximum of the peaks also decreases due to less phonons interaction [11]. The shift in Raman peaks gives the information of the stress level of the MWCNTs [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Lead zirconate titanate (PZT) is one of the most extensively used ferroelectric materials, owing to its excellent ferroelectric, dielectric, and piezoelectric properties. 8 The ferroelectric properties of PZT thin lms strongly depend on the electrode materials, in particularly the bottom electrode. To act as electrodes for ferroelectric thin lms, several conditions must be satised, such as: (1) the resistivity of electrode must be as low as possible; (2) the electrode must be chemically stable under high temperatures, not react with ferroelectrics during the fabrication process; (3) the electrode has strong adhesion with silicon substrate; (4) the electrode can provide a reasonable ferroelectric/electrode interface with suitable electronic contact; (5) the electrode plays a role in controlling the microstructure and orientation of ferroelectric thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that annealing at 600 °C resulted in damage to the CNT lattice and reaction between the substrate and CNTs. Ashok et al , using pulsed-laser deposition (PLD) under controlled oxygen partial pressure (70–80 mTorr) successfully coated MWCNTs with PZT at ∼550 °C and with 150–200 nm Ba 0.7 Sr 0.3 TiO 3 (BST) at 650 °C. In addition, Yang et al used PLD to form coaxial multiferroic nanowires of MWCNTs with CoFe 2 O 3 and BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%